2018
DOI: 10.1016/j.gaitpost.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Gait analysis in patients with chronic obstructive pulmonary disease: a systematic review

Abstract: Background: Gait instability is a major fall-risk factor in patients with chronic obstructive pulmonary disease (COPD). Clinical gait analysis is a reliable tool to predict fall onsets. However, controversy still exists on gait impairments associated with COPD. Research question: Thus, the aims of this review were to evaluate the current understanding of spatiotemporal, kinematic and kinetic gait features in patients with COPD. Methods: In line with PRISMA guidelines, a systematic literature search was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 45 publications
(128 reference statements)
0
14
1
Order By: Relevance
“…Many studies showed that patients with COPD present difficulties in maintaining upright standing 13 , 47 51 and stable walking 11 , 12 , 47 , 52 , 53 , with increased risk of falling 11 , 12 , 54 58 . Although the identification of specific causes for these motor disabilities is an open discussion 1 , most of the authors consider muscle weakness and limited oxygen supply as the main factors responsible for gait and balance alterations 13 , 47 , 50 , 54 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that patients with COPD present difficulties in maintaining upright standing 13 , 47 51 and stable walking 11 , 12 , 47 , 52 , 53 , with increased risk of falling 11 , 12 , 54 58 . Although the identification of specific causes for these motor disabilities is an open discussion 1 , most of the authors consider muscle weakness and limited oxygen supply as the main factors responsible for gait and balance alterations 13 , 47 , 50 , 54 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Gait assessment may be of clinical value as gait abnormalities have been reported in patients with COPD, including reduced cadence, reduced stride length and increased double support time as compared to healthy subjects [3,4,5,6,7]. Though PR has proven to increase gait speed in patients with COPD [39], a comprehensive analysis of gait characteristics after PR is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Walking has been reported as a problematic activity in daily life in patients with chronic obstructive pulmonary disease (COPD) [1,2]. Patients with COPD are characterized by gait alterations as compared to healthy older adults [3,4,5,6,7]. These gait alterations, in particular changes in the inherent stride-to-stride fluctuations, have been associated with non-communicable diseases [8,9] and falls in the aging population [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review of seven studies comprising 375 elderly patients (64-75 years) with predominantly severe COPD, Zago et al reported that gait abnormalities observed in these patients comprised of reduced step length and rhythm, and spatiotemporal inconsistency in gait patterns during ambulation. 8 In addition, Morlino et al proposed that aberrant gait and balance kinematics observed in patients with severe COPD could be related, in part, to damaged neuronal circuits that subserve those functional outcomes in the brain. 2 Despite recent progress in medical research, the pathogenesis of aberrant gait and balance kinematics observed in patients with severe COPD remains elusive.…”
mentioning
confidence: 99%